THE INFLUENCE OF ORGANIZATIONAL CULTURE AND WORK MANAGEMENT SYSTEM TO ORGANIZATIONAL COMMITMENT - Edward Edward; Rio Lesmana Rafar; Adi Putra (Journal of Business Studies and Management Review, 2017)
The purpose of this research are: (1) To know the description of organizational culture, management system to Employees commitment at Jambi Provincial Transportation Department. (2) To know the influence of organizational culture on Organization commitment to Jambi Provincial Transportation Department. (3) work management system to Organization commitment to Jambi Provincial Transportation Department (4) To know the influence between organizational culture and management system to Organization commitment at Jambi Provincial Transportation Department. The method of analysis of this research is descriptive and quantitative. The population in the study were the employees of Jambi Provincial Transportation Department. Technique of sampling research using technique of Stratified Sampling. The total sample in this study was 123 respondents. The data were analyzed using 2 (two) ways, namely (1) Using multiple linear regression to find out the factors that influence Organization commitment with t test and F test at significance level (α = 0,05). The result of the research shows that average level of respondent's answer for organizational culture variable (X1) is 60,94 and average level of respondent answer for work management system variable (X2) is 66,41, it shows highest level. The magnitude of influence of organizational culture variable and work management system on Organization commitment at Jambi Provincial Transportation Department is 6,333 (X1) and 3,685 (X2). From the test results simultaneously can be seen that the organizational culture variables and management systems work together have a significant influence on organizational commitment. Meanwhile, it is also known that work management system variables are more dominant in influencing Employees commitment to Jambi Provincial Transportation Department. Keywords: organizational culture, work management system, Organization commitment